A large-scale, multicentre, double-blind trial of ursodeoxycholic acid in patients with chronic hepatitis C. Issue 12 (15th June 2007) - Omata, Masao; Yoshida, Haruhiko; Toyota, Joji; Tomita, Eiichi; Nishiguchi, Shuhei; Hayashi, Norio; Iino, Shiro; Makino, Isao; Okita, Kiwamu; Toda, Gotaro; Tanikawa, Kyuichi; Kumada, Hiromitsu
Abstract : Background: Combined pegylated interferon and ribavirin has improved chronic hepatitis C (CH-C) therapy; however, sustained virological response is achieved in only about half of the patients with a 1b genotype infection. We assessed oral ursodeoxycholic acid (UDCA) on serum biomarkers as a possible treatment for interferon non-responders. Methods: CH-C patients with elevated alanine aminotransferase (ALT) were assigned randomly to 150 (n = 199), 600 (n = 200) or 900 mg/day (n = 197) UDCA intake for 24 weeks. Changes in ALT, aspartate aminotransferase (AST) and gamma-glutamyl transpeptidase (GGT) were assessed. This study is registered at ClinicalTrial.gov, identifier NCT00200343. Results: ALT, AST and GGT decreased at week 4 and then remained constant during drug administration. The median changes (150, 600 and 900 mg/day, respectively) were: ALT, −15.3, −29.2 and −36.2%; AST, −13.6, −25.0 and −29.8%; GGT, −22.4, −41.0 and −50.0%. These biomarkers decreased significantly less in the 150 mg/day than in the other two groups. Although changes in ALT and AST did not differ between the 600 and 900 mg/day groups, GGT was significantly lower in the 900 mg/day group. In subgroup analysis, ALT decreased significantly in the 900 mg/day group when the baseline GGT exceeded 80 IU/l. Serum HCV-RNA did not change in any group. Adverse effects were reported by 19.1% of the patients, with no differences between groups. Conclusions: A 600 mg/day UDCA dose was optimal to decrease ALT and AST levels in CH-C patients. The 900 mg/day dose decreased GGT levels further, and may be preferable in patients with prevailing biliary injuries.